"O Concílio dos Deuses” de Os Lusíadas em versões adaptadas da epopeia de Camões - Lima, Marta Ginólia Barreto (2019)
The purpose of this study is to analyze the presence of The Council of the Gods from Os Lusíadas in three adapted versions of Camões’ epic in prose and destined to children and juvenile public: one was written by Rubem Braga and Edson Rocha Braga; one by Luiz Maria Veiga; and one by Ricardo Vale, with the main objective of discussing the permanence or not of epic peculiarities from Os Lusíadas in the book adaptations in question through the recognition of the forms of retextualization used by the authors. It is also intended to measure the influence of adaptations of the epic genre on literary reading practices in childhood and adolescence. Firstly, the reflection will address the issue of literary reading in school, seeking to understand the "to be or not to be" of adapted literature. To do so, we will analyze how the book adaptations approached the selected episode of Os Lusíadas, taking into account both the aesthetic aspects and the resizing of content, with special emphasis on the presence of Roman gods in Camões’ epic. The analysis will be based on the detailed observation of the original work, in order to verify, in the adaptations, the processes of reduction of the original plot and the possible creative interferences, relating them to different forms of retextualization, based on the theoretical and critical contributions of Marilise Rezende Bertin (2008), Maria Alice Gonçalves Antunes (2007) and Dell'Isola (2007). Considerations about the epic genre, in turn, will be supported by Anazildo Vasconcelos da Silva's Teoria Épica do Discurso, in Christina Ramalho's Poemas Épicos: estratégias de leitura (2013), and also Leo Pollmann (1973) and his formulations about the epic and the Camonian epic. The following contributions are also noteworthy: Maria do Rosário Mortatti Magnani (2001), who offers a reflection on the formation of literary taste; Silvério Benedito (1997), who elaborates critical considerations about Camões epic; and José Cardoso Bernardes and Rui Afonso Mateus (2013), in their work Literatura e ensino do português. With this approach, we intend to contribute to the formation of a critical corpus on the phenomenon of literary adaptation and to measure it as one of the main segments of the mythological plan of Os Lusíadas makes sense in prose works of children's and juvenile’s literature.